Monoteísmo originário: linguagem, identidade e contracultura a partir de Hebreus - Santos, Douglas Oliveira dos (2019)
Inquiries about the origin of monotheism of the Hebrew people perpetuate in academic discourses. Systematic theologies take up the conciliar Christological concepts to explain Jesus in a monotheistic framework. From this perspective, the theme of this research is the perception of monotheism in the first century, which has as its object monotheism in Letter to the Hebrews. The general objective is to analyze the conception of the Sacred in the formation of Christianity, with the discourses of the construction of a one deity, taking the Letter to the Hebrews as the main source. The specific objectives are to understand the foundation of monotheistic construction in its genesis; to show that the final redactor used an older source to ground his perceptions of Jesus, to understand the terms theos e Kyrios ( ); to present whether there is an association of these words with the Hebrew terms Elohim ( ) and Iahweh ( ), and whether there is a connection between Jesus and Iahweh ( ) in the Original Monotheism; to show how the Final Redactor united past and present of that time and how the Original Monotheism was perceived in the construction of paradigms; to elucidate the collective understanding of redeemed memory through epistemology and through a rereading and re-signification of Jewish traditions. The main question raised is how does the Original Monotheism constitute itself, based on the analyses of the Letter to the Hebrews? The hypothesis considers that the literature presented in the Letter to the Hebrews clarifies the theme and the proposed objectives. The qualitative methodology follows the clarification with the analysis of the languages, the philosophical contrapositions and the historical perspective, that substantiate with the foundations. Amongst the Theorists are Von Rad (1986), Stegemann and Stegemann (2004), Koester (2005) and Malina (2004) and others. The work divided into three chapters brings the first result that is related to a process of materialization of history, in which linguistic research shows its development, whose views center on the theme of the Original Monotheism. The second result is the perspective on dating the work of Letter to the Hebrews, written at different times, before and after AD 70. Thus, the relevance of this thesis lies in understanding how the Christian imagery of the Sacred was built during this period and was consolidated in the history of Christianity. In the Christian segments, various biblical interpretations were established, allowing spaces for discussions in the Sciences of Religion sphere